Metal composite material and preparation method thereof

By using metal composite materials such as iron, cobalt, nickel, silicon, copper, etc., and combining electrospinning technology to prepare nitrogen-doped spiral carbon nanofibers and carbon nanotubes, the problems of poor absorption performance and insufficient corrosion resistance of alloy wave absorbing materials in a wide frequency range are solved, and efficient electromagnetic wave absorption and good thermal stability and chemical resistance are achieved.

CN119913412APending Publication Date: 2025-05-02SHANDONG BOREN NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510112343.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-05-02

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of metal materials, in particular to a metal composite material and a preparation method thereof. The material comprises the following components in parts by mass: 10-15 parts of iron, 8-18 parts of cobalt, 20-30 parts of nickel, 12-25 parts of silicon, 4-12 parts of copper and 20-40 parts of a functional additive, the functional additive is helical carbon nanofibers with carbon nanotubes generated in situ. The metal composite material provided by the invention has an excellent wave-absorbing function and is relatively high in thermal stability and chemical resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal materials, and in particular relates to a metal composite material and a preparation method thereof. Background Art

[0002] Absorbing materials are functional materials that can effectively absorb and attenuate electromagnetic waves, and convert electromagnetic wave energy into other forms of energy through some internal interaction mechanisms. They have important research and application value in both civil and military fields. With the continuous research and development of electromagnetic absorbing materials, the types of absorbing materials tend to be diversified and complex, requiring them to develop in the direction of composite, intelligent and broadband. Alloy absorbing materials are key members of the absorbing material family, relying on the unique electromagnetic properties of alloys to effectively absorb electromagnetic waves. Alloy absorbing materials generally include iron-based alloys, Permalloy, etc., but a single alloy absorbing material is difficult to maintain good absorbing performance in a wide frequency range. It can usually only have a good absorption effect on electromagnetic waves in a specific frequency band, and it is difficult to meet the requirements for broadband absorbing in complex electromagnetic environments. In addition, alloy absorbing materials are prone to chemical reactions such as oxidation and corrosion in humid, acidic and alkaline corrosive environments, thereby affecting their absorbing performance and service life. For example, iron-based alloys are prone to rust in humid air, resulting in a decrease in magnetic properties. In addition, under high temperature environment, the magnetic and dielectric properties of alloy absorbing materials may change, resulting in reduced magnetic permeability and changed dielectric constant, which will make the absorbing effect worse. For example, some alloys will undergo phase change or grain growth after exceeding a certain temperature, affecting their electromagnetic loss mechanism.

[0003] For example, CN115896516A discloses a micro-nano magnetic high entropy alloy absorbing material and a preparation method thereof, comprising the following steps: (1) weighing Fe, Co, Ni, Cr, and Cu powders and mixing them evenly; (2) using a planetary ball mill for room temperature ball milling; (3) continuously passing liquid nitrogen through the outer wall of the ball milling tank and performing low temperature ball milling; (4) subjecting the milled alloy powder to pulse magnetic field treatment and / or cryogenic treatment to obtain a micro-nano magnetic high entropy alloy absorbing material. This application uses Fe, Co, Ni, Cr, and Cu to mechanically alloy to form a stable single-phase magnetic high entropy alloy, and refines the powder particle size by room temperature + liquid nitrogen low temperature ball milling to enhance the absorbing performance, but the absorbing range of this application is limited and the chemical resistance is poor.

[0004] For example, CN118531586A discloses a nitrogen-doped porous carbon nanofiber-high entropy alloy composite absorbing material, preparation method and application thereof; the components of the composite absorbing material include: porous nitrogen-doped carbon nanofibers and high entropy alloy nanoparticles; the composite absorbing material is prepared by electrostatic spinning technology and Joule heat technology; the porous nitrogen-doped carbon nanofibers are one-dimensional nitrogen-doped porous structure fibers; the high entropy alloy nanoparticles are loaded on the porous nitrogen-doped carbon nanofibers. The one-dimensional porous carbon nanofibers in the application are interconnected to form a three-dimensional mesh structure, which is beneficial to multiple refraction and scattering of electromagnetic waves; wherein the porous structure is beneficial to reducing the overall density of the composite material and increasing the specific surface area of ​​the composite material; wherein the high entropy effect of the high entropy alloy can make the local polarization inside the alloy improve the polarization loss capacity of the composite material. However, in fact, the interface bonding force between the alloy and the one-dimensional nitrogen-doped porous structure fiber may be weak, and the alloy particles are prone to fall off or agglomeration during use. And the pre-oxidation calcination adopted by it weakens the interaction between the alloy and the carbon nanofiber, and the grains of the alloy will grow, thereby affecting the thermal stability of the material.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a metal composite material and a preparation method thereof. The metal composite material provided by the present invention has excellent wave absorbing function and has strong thermal stability and chemical resistance.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] In a first aspect, an embodiment of the present invention provides a metal composite material, comprising the following components by mass: 10-15 parts of iron, 8-18 parts of cobalt, 20-30 parts of nickel, 12-25 parts of silicon, 4-12 parts of copper, and 20-40 parts of functional additives;

[0009] The functional additive is a spiral carbon nanofiber with in-situ generated carbon nanotubes.

[0010] The metal compounded by the invention has excellent wave absorbing function, and the obtained composite material has good thermal stability and chemical resistance.

[0011] In terms of wave absorption function, iron, cobalt, and nickel are all magnetic metals with high magnetic permeability. In the wave absorption process, electromagnetic waves can be effectively absorbed through magnetic loss mechanisms such as hysteresis loss and eddy current loss, while silicon itself has certain dielectric properties, which can increase the dielectric constant of the material, generate dielectric loss under the action of the electric field, and complement the magnetic loss of iron, cobalt, and nickel, so that the material absorbs electromagnetic waves more comprehensively. In addition, the copper added in this application has good electrical conductivity, which can enhance the conduction current inside the material, thereby increasing the conductivity loss and improving the effect of dielectric loss. At the same time, there is a certain electromagnetic coupling effect between it and magnetic metals such as iron, cobalt, and nickel, which further optimizes the wave absorption performance. In addition, the addition of iron, cobalt, and nickel magnetic metals can adjust the magnetic permeability of the material, while silicon and copper can adjust the dielectric constant of the material. The ratio of iron, cobalt, nickel, silicon, and copper set by the present invention makes the impedance of the material better match the impedance of the free space, reduces the reflection of electromagnetic waves on the surface of the material, and enables more electromagnetic waves to enter the material and be absorbed. It is further explained that the composite structure formed by iron, cobalt and nickel produces a unique microstructure and interface, which increases the scattering and absorption path of electromagnetic waves. Silicon can be used as a matrix or coating material. Through the preparation method of the present invention, it can be used to wrap metals such as iron, cobalt and nickel to form a core-shell structure. These structures can not only increase the stability of the material, but also produce interface polarization and multiple scattering between different phases, thereby improving the wave absorption performance. Copper can be used as part of the conductive network to promote the conduction and transfer of electrons. At the same time, the interface between it and other metals may also produce additional electromagnetic interactions, thereby enhancing the wave absorption effect.

[0012] In terms of thermal stability, iron, cobalt, and nickel can form an infinite solid solution, which improves the thermal stability of the material. Silicon can form stable silicide phases in alloys, such as FeSi, CoSi, etc. These silicide phases have high melting points and thermal stability, and can maintain the structural integrity and performance stability of the material at high temperatures. Copper can also play a role in refining grains in alloys, thereby improving the thermal stability of the material. At the same time, cobalt and nickel have antioxidant properties and can form a dense oxide film at high temperatures to prevent oxygen from further diffusing into the material. Silicon can improve the material's antioxidant ability, and its oxidation product SiO 2 It can play a certain protective role.

[0013] In terms of chemical resistance, a passivation film can be formed in a corrosive environment of iron, cobalt, and nickel. For example, in an oxidizing acid, a dense oxide film will form on the surface of iron, cobalt, and nickel to prevent the corrosive medium from further reacting with the metal matrix. Silicon can promote the formation and stability of the passivation film. At the same time, the addition of silicon can also change the structure and properties of the corrosion product, making it more dense and stable, thereby improving the corrosion resistance of the material. Copper can also form a protective film in a corrosive environment to slow down the corrosion rate. In addition, when metals such as iron, cobalt, nickel, and copper form a composite material, micro-batteries will be formed inside the material due to their different electrode potentials. Through the compounding of the present invention, a stable phase structure and interface can be formed between metals, reducing the corrosion effect of micro-batteries. Silicon plays a role in adjusting the alloy composition and organizational structure, reducing the potential difference between different metal phases, thereby improving the chemical corrosion resistance of the material.

[0014] In a preferred embodiment, the preparation method of the functional additive is as follows:

[0015] Polyacrylonitrile and N,N-dimethylformamide are mixed and stirred, and then nickel acetate is added for electrostatic spinning to obtain electrostatically spun fibers, and then heat stabilization treatment is performed to obtain a solid phase. The solid phase is mixed with melamine and reacted once, and then acetylene gas is introduced for a secondary reaction, and the functional additive is obtained by cooling, washing, grinding and sieving.

[0016] In a preferred embodiment, the mass ratio of polyacrylonitrile, N,N-dimethylformamide and nickel acetate is 1:(50-100):(5-20).

[0017] In a preferred embodiment, the stirring conditions are: stirring temperature is 40-60° C., and stirring time is 3-6 h.

[0018] In a preferred embodiment, the heat stabilization treatment is carried out under the conditions of: keeping the temperature at 200-300° C. for 1-3 hours.

[0019] In a preferred embodiment, the mass ratio of the solid phase to melamine is 1:(1.2-1.9).

[0020] In a preferred embodiment, the conditions of the primary reaction are: reacting at a temperature of 600-800° C. for 1-3 h under an argon atmosphere.

[0021] In a preferred embodiment, the secondary reaction is carried out at a temperature of 700-900° C. for 15-40 min.

[0022] In a preferred embodiment, the sieve used for screening is 100-300 mesh.

[0023] The present invention directly prepares nitrogen-doped spiral carbon nanofibers through electrospinning technology, and directly generates carbon nanotubes on the nitrogen-doped spiral carbon nanofibers, so that the carbon nanotubes are directly embedded in the surface of the spiral carbon nanofibers, thereby preventing the problems of agglomeration and phase separation of the structures of the two when the two are directly mixed, and further synergizing with metals to improve the material's wave absorption performance.

[0024] Specifically, carbon nanotubes are very easy to entangle and agglomerate with each other due to their large aspect ratio, high specific surface area and intermolecular forces, forming aggregates at the micron or even millimeter level. Nitrogen-doped spiral carbon nanofibers also have a certain aspect ratio. When the two are simply mixed, this agglomeration phenomenon becomes more serious, making it difficult to achieve uniform dispersion, resulting in large performance differences between the various parts inside the composite material, and unable to give full play to their respective advantages. In addition, the two have different surface energies and chemical activities, and direct mixing is difficult to ensure stable coexistence in the matrix material, and phase separation is prone to occur, resulting in unstable material performance and the inability to stably output functions such as wave absorption. The preparation method of the present invention just overcomes this point.

[0025] It should also be noted that the doping of nitrogen atoms in nitrogen-doped spiral carbon nanofibers can introduce defects and change the electronic structure of fibers, increase the number of dipoles and polarization inside the fibers, and make the fibers produce more dielectric losses under the action of electromagnetic fields. And carbon nanotubes themselves have higher electrical conductivity and dielectric constant, and can produce significant dielectric losses in electromagnetic fields, mainly due to their unique one-dimensional structure and electronic delocalization characteristics, so that the movement of electrons in carbon nanotubes is restricted, thereby producing polarization relaxation losses, etc. When carbon nanotubes are generated in situ on nitrogen-doped spiral carbon nanofibers, the dielectric loss mechanisms of the two are superimposed and enhanced on each other, so that composite materials produce effective dielectric losses in a wider frequency range, and improve the absorption capacity of electromagnetic waves. In addition, although spiral carbon nanofibers themselves may not have obvious magnetic loss characteristics, nitrogen doping can change their electronic spin states or interact with other magnetic elements, thereby introducing magnetic loss mechanisms. Carbon nanotubes also have certain magnetic losses at the same time, and especially through the composite of alloys of the present invention and functional additives, magnetic losses are strengthened. In addition, the special structure and electron cloud distribution of carbon nanotubes may affect the distribution of the surrounding magnetic field and generate additional magnetic losses. The in-situ generation of carbon nanotubes on nitrogen-doped spiral carbon nanofibers makes the magnetic losses of the two complement each other, and work together with dielectric losses to achieve multi-mechanism absorption of electromagnetic waves and improve the performance of wave absorbing materials. Further in terms of impedance matching optimization, nitrogen doping can adjust the dielectric constant and conductivity of spiral carbon nanofibers, thereby affecting the impedance matching degree between them and free space. The nitrogen doping amount of the present invention can make the impedance of spiral carbon nanofibers closer to the impedance of free space, reducing the reflection of electromagnetic waves on the surface of the material. At the same time, the presence of carbon nanotubes can further adjust the dielectric constant and conductivity of the composite material, and its high conductivity and special one-dimensional structure can improve the impedance matching characteristics of the material to a certain extent. After the carbon nanotubes are in-situ generated on nitrogen-doped spiral carbon nanofibers, the synergistic effect of the two can more accurately adjust the impedance of the composite material, so that it can achieve good matching with free space in a wider frequency range, thereby improving the incident efficiency and absorption efficiency of electromagnetic waves. Furthermore, nitrogen-doped helical carbon nanofibers have a special helical structure, which can increase the propagation path and scattering times of electromagnetic waves inside the material, causing electromagnetic waves to continuously reflect and refract inside the fiber, thereby improving the absorption efficiency. The one-dimensional tubular structure and high aspect ratio of carbon nanotubes can form a network or bundle-like microstructure in the composite material, increasing the scattering center and scattering cross section of electromagnetic waves. At the same time, the interface between carbon nanotubes and nitrogen-doped helical carbon nanofibers will also produce a scattering effect. The in-situ generation of carbon nanotubes on nitrogen-doped helical carbon nanofibers can construct a more complex and diverse microstructure. The structural advantages of the two are combined to produce a stronger scattering effect, making the propagation of electromagnetic waves inside the material more complex and tortuous, and increasing the probability of electromagnetic wave absorption.

[0026] In addition, the in-situ generated carbon nanotubes grow on nitrogen-doped spiral carbon nanofibers to form a unique multi-level structure. The alloy nanoparticles are loaded on this composite fiber, which further increases the complexity and diversity of the material. This multi-level structure can cause electromagnetic waves to be reflected, refracted and scattered multiple times, extending the propagation path of electromagnetic waves inside the material, thereby increasing the absorption probability of electromagnetic waves; at the same time, there is a strong chemical bonding or physical adsorption between the in-situ generated carbon nanotubes and the nitrogen-doped spiral carbon nanofibers, so that the interface between the two is tightly bonded. When the alloy is combined with this composite fiber, the carbon nanotubes and the nitrogen-doped spiral carbon nanofibers can act as a bridge to promote the interface bonding between the alloy and the fiber, reduce interface defects and scattering centers, and help improve the overall performance and wave absorption effect of the material. In addition, carbon nanotubes have excellent electrical conductivity and a high dielectric constant, and can produce polarization relaxation in an electromagnetic field, thereby causing dielectric loss. Nitrogen doping can introduce defects and impurity energy levels into the spiral carbon nanofibers, further increasing the dielectric loss. The addition of alloys can adjust the dielectric constant and magnetic permeability of the composite material, so that it can achieve better impedance matching in a wider frequency range and improve the absorption efficiency of electromagnetic waves. In addition, since the alloy compounded by the present invention has good magnetic properties, magnetic loss mechanisms such as hysteresis loss, eddy current loss and natural resonance will be generated in the electromagnetic field, which will cooperate with the dielectric loss of carbon nanotubes and nitrogen-doped helical carbon nanofibers to achieve complementary electromagnetic loss. In the high frequency band, the dielectric loss of carbon nanotubes is dominant; in the low frequency band, the magnetic loss of the alloy plays an important role, thereby broadening the effective absorption band of the absorbing material.

[0027] In a second aspect, an embodiment of the present invention provides a method for preparing a metal composite material, comprising the following steps:

[0028] Iron powder, cobalt powder, nickel powder, silicon powder and copper powder are mixed and ball-milled once under vacuum, and then functional additives are added and ball-milled twice to obtain a metal composite material.

[0029] In a preferred embodiment, the conditions for the first ball milling are: a ball-to-material ratio of (4-8): 1, a ball milling speed of 200-400 r / min, a ball milling time of 12-36 h, and anhydrous ethanol is added during ball milling, wherein the amount of anhydrous ethanol added is 10wt%-20wt% of the total mass of iron powder, cobalt powder, nickel powder, silicon powder, and copper powder.

[0030] In a preferred embodiment, the secondary ball milling conditions are: ball-to-material ratio is (4-8):1, ball milling speed is 500-700 r / min, and ball milling time is 2-4 h.

[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0032] 1. The metal compounded in the present invention has excellent wave absorbing function, and the obtained composite material has good thermal stability and chemical resistance.

[0033] 2. The present invention directly prepares nitrogen-doped spiral carbon nanofibers through electrospinning technology, and directly generates carbon nanotubes on the nitrogen-doped spiral carbon nanofibers, so that the carbon nanotubes are directly embedded in the surface of the spiral carbon nanofibers, thereby preventing the agglomeration and phase separation of the two structures when the two are directly mixed, and further synergizes with metals to improve the material's wave absorption performance.

[0034] 3. The functional additives provided by the present invention and the raw materials synergistically improve the wave absorption performance, thermal stability and chemical resistance of the composite material. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Unless otherwise specified, the raw materials and reagents used in the present invention are commercially available.

[0037] Iron powder, with an average particle size of 100 nm, was purchased from Wuhan Iron and Steel Powder Metallurgy Co., Ltd.;

[0038] Cobalt powder, with an average particle size of 100 nm, was purchased from Hanrui Cobalt Industry;

[0039] Nickel powder, with an average particle size of 100 nm, was purchased from Jiangsu Boqian New Materials Co., Ltd.;

[0040] Silicon powder, with an average particle size of 100 nm, was purchased from Tonghua Shuanglong Chemical Co., Ltd.;

[0041] Copper powder, with an average particle size of 100 nm, was purchased from Hangzhou Xinchuan New Materials Co., Ltd.

[0042] Example 1

[0043] This embodiment provides a method for preparing a metal composite material, comprising the following steps:

[0044] (1) Preparation of functional additives

[0045] In parts by mass, 1 part of polyacrylonitrile and 100 parts of N,N-dimethylformamide are mixed and stirred at a stirring temperature of 50°C for 4 hours, and then 20 parts of nickel acetate are added for electrostatic spinning. Specifically, the above liquid phase is loaded into a disposable syringe, and transported by a syringe pump at a constant flow rate of 0.3 ml / h, a grounded aluminum foil is used as a collector, and the distance between the needle tip and the aluminum foil is maintained at 15 cm. A DC voltage of 20 kV is applied between the needle tip and the aluminum foil to obtain electrostatically spun fibers, and then the fibers are kept at a temperature of 220°C for 1.5 hours for heat stabilization to obtain a solid phase. After mixing 1 part of the solid phase with 1.5 parts of melamine, the mixture is reacted at a temperature of 700°C for 2 hours under an argon atmosphere, and then acetylene gas is introduced to react at a temperature of 750°C for 20 minutes, and the fibers are cooled, washed, and ground through a 200-mesh sieve to obtain a functional additive.

[0046] (2) Preparation of metal composite materials

[0047] By mass, 12 parts of iron powder with an average particle size of 100 nm, 10 parts of cobalt powder with an average particle size of 100 nm, 22 parts of nickel powder with an average particle size of 100 nm, 15 parts of silicon powder with an average particle size of 100 nm, and 7 parts of copper powder with an average particle size of 100 nm are mixed and ball-milled once under vacuum. The conditions for the first ball milling are: a ball-to-material ratio of 6:1, a ball milling speed of 300 r / min, and a ball milling time of 24 h. Anhydrous ethanol is added during ball milling, and the amount of anhydrous ethanol added is 12 wt% of the total mass of iron powder, cobalt powder, nickel powder, silicon powder, and copper powder. Then, 25 parts of functional additives are added for secondary ball milling. The conditions for the secondary ball milling are: a ball-to-material ratio of 6:1, a ball milling speed of 600 r / min, and a ball milling time of 2.5 h. After cooling, a metal composite material is obtained.

[0048] Example 2

[0049] This embodiment provides a method for preparing a metal composite material, comprising the following steps:

[0050] (1) Preparation of functional additives

[0051] In parts by mass, 1 part of polyacrylonitrile and 100 parts of N,N-dimethylformamide are mixed and stirred at a stirring temperature of 55°C for 4 hours, and then 20 parts of nickel acetate are added for electrostatic spinning. Specifically, the above liquid phase is loaded into a disposable syringe, and transported by a syringe pump at a constant flow rate of 0.3 ml / h, a grounded aluminum foil is used as a collector, and the distance between the needle tip and the aluminum foil is maintained at 15 cm. A DC voltage of 20 kV is applied between the needle tip and the aluminum foil to obtain electrostatically spun fibers, and then the fibers are kept at a temperature of 280°C for 2.5 hours for heat stabilization to obtain a solid phase. After mixing 1 part of the solid phase with 1.7 parts of melamine, the mixture is reacted at a temperature of 750°C for 2 hours under an argon atmosphere, and then acetylene gas is introduced to react at a temperature of 850°C for 20 minutes, and the fibers are cooled, washed, and ground through a 200-mesh sieve to obtain a functional additive.

[0052] (2) Preparation of metal composite materials

[0053] By mass, 14 parts of iron powder with an average particle size of 100nm, 16 parts of cobalt powder with an average particle size of 100nm, 26 parts of nickel powder with an average particle size of 100nm, 22 parts of silicon powder with an average particle size of 100nm, and 10 parts of copper powder with an average particle size of 100nm are mixed and ball-milled once under vacuum. The conditions for the first ball milling are: a ball-to-material ratio of 6:1, a ball milling speed of 300r / min, and a ball milling time of 24h. Anhydrous ethanol is added during ball milling, and the amount of anhydrous ethanol added is 18wt% of the total mass of iron powder, cobalt powder, nickel powder, silicon powder, and copper powder. Then, 35 parts of functional additives are added for secondary ball milling. The conditions for the secondary ball milling are: a ball-to-material ratio of 6:1, a ball milling speed of 600r / min, and a ball milling time of 2.5h. After cooling, a metal composite material is obtained.

[0054] Comparative Example 1

[0055] The difference between this comparative example and Example 1 is that no functional additive is added, and the mass proportions of iron powder, cobalt powder, nickel powder, silicon powder and copper powder are changed to 17 parts, 15 parts, 27 parts, 20 parts and 12 parts respectively.

[0056] Comparative Example 2

[0057] The difference between this comparative example and Example 1 is that the preparation method of the functional additive is changed to the following:

[0058] In parts by mass, 1 part of polyacrylonitrile and 100 parts of N,N-dimethylformamide are mixed and stirred at a stirring temperature of 50°C for 4 hours, and then 20 parts of nickel acetate are added for electrostatic spinning. Specifically, the above liquid phase is loaded into a disposable syringe and transported by a syringe pump at a constant flow rate of 0.3 ml / h. A grounded aluminum foil is used as a collector, and the distance between the needle tip and the aluminum foil is maintained at 15 cm. A DC voltage of 20 kV is applied between the needle tip and the aluminum foil to obtain electrostatically spun fibers, and then the fibers are heat-stabilized at 220°C for 1.5 hours to obtain a solid phase. After mixing 1 part of the solid phase with 1.5 parts of melamine, the mixture is reacted at 700°C for 2 hours in an argon atmosphere to obtain nitrogen-doped spiral carbon nanofibers.

[0059] Comparative Example 3

[0060] The difference between this comparative example and Example 1 is that the preparation method of the functional additive is changed to the following:

[0061] By mass, 1 part of polyacrylonitrile and 100 parts of N,N-dimethylformamide were mixed and stirred at a stirring temperature of 50°C for 4 hours, and then 20 parts of nickel acetate were added for electrostatic spinning. Specifically, the above liquid phase was loaded into a disposable syringe and transported by a syringe pump at a constant flow rate of 0.3 ml / h. A grounded aluminum foil was used as a collector, and the distance between the needle tip and the aluminum foil was maintained at 15 cm. A DC voltage of 20 kV was applied between the needle tip and the aluminum foil to obtain electrostatically spun fibers, which were then kept at a temperature of 220°C for 1.5 hours for heat stabilization treatment to obtain a solid phase, and 1 part of the solid phase was reacted at a temperature of 700°C for 2 hours under an argon atmosphere to obtain spiral carbon nanofibers.

[0062] Comparative Example 4

[0063] The difference between this comparative example and Example 1 is that the preparation method of the functional additive is changed to the following:

[0064] In parts by mass, 1 part of polyacrylonitrile and 100 parts of N,N-dimethylformamide are mixed and stirred at a stirring temperature of 50°C for 4 hours, and then 20 parts of nickel acetate are added for electrostatic spinning. Specifically, the above liquid phase is loaded into a disposable syringe and transported by a syringe pump at a constant flow rate of 0.3 ml / h. A grounded aluminum foil is used as a collector, and the distance between the needle tip and the aluminum foil is maintained at 15 cm. A DC voltage of 20 kV is applied between the needle tip and the aluminum foil to obtain electrostatically spun fibers, and then the fibers are heat-stabilized at 220°C for 1.5 hours to obtain a solid phase. After mixing 1 part of the solid phase with 1.5 parts of melamine, the mixture is reacted at 700°C for 2 hours in an argon atmosphere to obtain nitrogen-doped spiral carbon nanofibers.

[0065] The nitrogen-doped helical carbon nanofibers and carbon nanotubes are directly mixed to obtain the functional additive, and the mass ratio of the nitrogen-doped helical carbon nanofibers and the carbon nanotubes is the same.

[0066] Comparative Example 5

[0067] The difference between this comparative example and Example 1 is that iron powder is not added, and the mass proportions of cobalt powder, nickel powder, silicon powder and copper powder are changed to 13 parts, 25 parts, 18 parts and 10 parts respectively.

[0068] Comparative Example 6

[0069] The difference between this comparative example and Example 1 is: the difference between this comparative example and Example 1 is: no cobalt powder is added, and the mass parts of iron powder, nickel powder, silicon powder and copper powder are changed to 14.5 parts, 24.5 parts, 17.5 parts and 9.5 parts respectively.

[0070] Comparative Example 7

[0071] The difference between this comparative example and Example 1 is: the difference between this comparative example and Example 1 is: nickel powder is not added, and the mass parts of iron powder, cobalt powder, silicon powder and copper powder are changed to 17.5 parts, 15.5 parts, 20.5 parts and 12.5 parts respectively.

[0072] Comparative Example 8

[0073] The difference between this comparative example and Example 1 is: the difference between this comparative example and Example 1 is: silicon powder is not added, and the mass proportions of iron powder, cobalt powder, nickel powder and copper powder are changed to 15.75 parts, 13.75 parts, 25.75 parts and 10.75 parts respectively.

[0074] Comparative Example 9

[0075] The difference between this comparative example and Example 1 is: the difference between this comparative example and Example 1 is: no copper powder is added, and the mass parts of iron powder, cobalt powder, nickel powder and silicon powder are changed to 13.4 parts, 11.4 parts, 23.4 parts and 16.4 parts respectively.

[0076] Performance Testing

[0077] The complex dielectric constant and complex magnetic permeability of the metal composite materials prepared in the embodiments and comparative examples were tested at 4 GHz and 16 GHz using an Agilent N5222A vector network analyzer. Finally, the reflection loss of the material to electromagnetic waves was calculated using transmission line theory. The results are shown in Table 1.

[0078] After the metal composite materials prepared in the embodiment and the comparative example were treated at 300°C, the complex dielectric constant and complex magnetic permeability of the samples were tested at 4 GHz and 16 GHz using an Agilent N5222A vector network analyzer. Finally, the reflection loss of the material to electromagnetic waves was calculated using transmission line theory. The results are shown in Table 1.

[0079] After the metal composite materials prepared in the embodiment and the comparative example were placed in a salt spray formed by a 5wt% NaCl solution for 8 hours, the complex dielectric constant and complex magnetic permeability of the samples at 4 GHz and 16 GHz were tested using an Agilent N5222A vector network analyzer. Finally, the reflection loss of the material to electromagnetic waves was calculated using transmission line theory. The results are shown in Table 1.

[0080] Table 1 Performance test results

[0081]

[0082] From the above performance test results, it can be seen that Examples 1-2 have good wave absorption performance, thermal stability and chemical resistance, especially Example 2 has the most outstanding comprehensive performance, which is mainly due to the synergistic effect between the compounded elements and functional additives of the present invention.

[0083] The comparative example does not adopt the necessary technical solution, resulting in its performance being significantly worse than that of the embodiment in the corresponding performance test. This better proves the irreplaceable nature of the specific technical solution of the present application in achieving technical effects and solving technical problems.

[0084] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A metal composite material, characterized in that: The composition comprises the following components by mass: 10-15 parts of iron, 8-18 parts of cobalt, 20-30 parts of nickel, 12-25 parts of silicon, 4-12 parts of copper, and 20-40 parts of functional additives; The functional additive is a spiral carbon nanofiber with in-situ generated carbon nanotubes.

2. The metal composite material according to claim 1, characterized in that: The preparation method of the functional additive is as follows: Polyacrylonitrile and N,N-dimethylformamide are mixed and stirred, and then nickel acetate is added for electrostatic spinning to obtain electrostatically spun fibers, and then heat stabilization treatment is performed to obtain a solid phase. The solid phase is mixed with melamine and reacted once, and then acetylene gas is introduced for a secondary reaction, and the functional additive is obtained by cooling, washing, grinding and sieving.

3. The metal composite material according to claim 2, characterized in that: The mass ratio of polyacrylonitrile, N,N-dimethylformamide and nickel acetate is 1:(50-100):(5-20).

4. The metal composite material according to claim 2, characterized in that: The stirring conditions are: stirring temperature is 40-60° C., and stirring time is 3-6 h.

5. The metal composite material according to claim 2, characterized in that: The conditions of the heat stabilization treatment are: keeping the temperature at 200-300° C. for 1-3 hours.

6. The metal composite material according to claim 2, characterized in that: The mass ratio of the solid phase to melamine is 1:(1.2-1.9); And / or, the sieve used for the sieving is 100-300 meshes.

7. The metal composite material according to claim 2, characterized in that: The conditions of the primary reaction are: reacting at a temperature of 600-800° C. for 1-3 h under an argon atmosphere; And / or, the secondary reaction is carried out under the conditions of: reacting at a temperature of 700-900° C. for 15-40 min.

8. A method for preparing the metal composite material according to any one of claims 1 to 7, characterized in that: Iron powder, cobalt powder, nickel powder, silicon powder and copper powder are mixed and ball-milled once under vacuum, and then functional additives are added and ball-milled twice to obtain a metal composite material.

9. The method for preparing the metal composite material according to claim 8, characterized in that: The conditions for the first ball milling are as follows: a ball-to-material ratio of (4-8):1, a ball milling speed of 200-400 r / min, a ball milling time of 12-36 h, and anhydrous ethanol is added during ball milling, wherein the amount of anhydrous ethanol added is 10wt%-20wt% of the total mass of iron powder, cobalt powder, nickel powder, silicon powder and copper powder.

10. The method for preparing the metal composite material according to claim 8, characterized in that: The secondary ball milling conditions are as follows: ball-to-material ratio is (4-8):1, ball milling speed is 500-700r / min, and ball milling time is 2-4h.

Citation Information

Patent Citations

  • Micro-nano magnetic high-entropy alloy wave-absorbing material and preparation method thereof

    CN115896516A

  • Nitrogen-doped porous carbon nanofiber-high-entropy alloy composite wave-absorbing material as well as preparation method and application thereof

    CN118531586A